Knockdown of MPP8 suppresses cell proliferation via regulation of HOXA5 in non-small cell lung cancer cells - Gao, Xiang-Yang; Qiao, Yu-Li; Zhang, Yu; Wang, Jun; Shen, Xu; Xu, Chun-Wei (Cellular and Molecular Biology, 2018)
M-phase phosphoprotein 8 (MPP8) is reported to be closely implicated in cancer initiation and progression. In addition, the homeobox gene HOXA5 has been shown to play critical roles in hematopoiesis, embryogenesis, and tumorigenesis. Nevertheless, the functional relevance of MPP8 and it’s relation with HOXA5 in non-small cell lung cancer (NSCLC) is unknown. Therefore, the present study aimed to detect the expression profile of MPP8 in NSCLC and further explore it’s biological roles in lung cancer cells. Cell proliferation was measured by CCK-8 assay and EdU incorporation assay. Real-time PCR was applied to detect the mRNA expression of MPP8 and HOXA5. The protein levels of MPP8 and HOXA5 were evaluated by western blot. Our study found that the expression of MPP8 was significantly increased in the NSCLC tissue compared with the adjacent non-tumorous tissue. Compared with the human lung fibroblasts, the elevated gene expression of MPP8 was also detected in the human NSCLC cell lines including NCI-H23 and NCI-H1299. In addition, knockdown of MPP8 led to an obvious reduction in cell viability and DNA synthesis in NCI-H23 and NCI-H1299 cells. Furthermore, down-regulation of MPP8 resulted in elevated expression of HOXA5 in NSCLC cells both at the mRNA and protein levels. Moreover, depletion of HOXA5 abolished the anti-tumor function of MPP8 knockdown in NSCLC cells. The present study demonstrated that MPP8 was associated with NSCLC cell proliferation through regulation of HOXA5, suggesting that MPP8 may act as a novel therapeutic target for treatment of NSCLC.